Estudo da ação do medicamento arsenicum album na mucosa oral acometida por estomatite aftosa recorrente - Proença, Alessandra Müzel Ibrahim (2009)
A cold sore is a common condition, affecting much of the population and usually produce pain and discomfort. According to dentists of the Oral Health Program of Itapeva, none of the treatments used to date been unsuccessful expected effect. This fact justifies the need to develop more work in this area. We'll do an experiment using a homeopathic treatment for 30 days at no cost to the patient. For comparative purposes, some of the bottles randomly distributed not contain drug, only inert substance. The patient must daily put 5 drops of the vial contents beneath the tongue, then get up and must wait half an hour to take the breakfast or brushing teeth. After 15 days of the drug, the dentist will make a second visit to evaluate the results (healing of sores or appearance of others). After 30 days, the dentist will perform a Last Delivery consultation to assess the treatment outcome. Any changes in the oral mucosa or unwanted effects that occur during the 30 days of treatment, should be brought to the attention of their dentist so that it performs clinical examination and give continuity or not the treatment in this patient.